EFFICACY OF IGRS COMPOUND TRIFLUMURON AND METHOPRENE AGAINST Culex quinquefasciatus MOSQUITO LARVAE AND PUPAL CONTROL IN POOLS, DRAINS AND TANKS - RAJASEKAR, P.; MEERAMAIDEEN, M.; SALAHUDEEN, M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Triflumuron and Methoprene, insect growth regulators (IGRs) were highly effective against Cx. quinquefasciatus (Say) larvae and pupae in pools, drains and tanks at the dosages of 0.04 and 0.4 mg/l. To determine the most appropriate field study assessment was made by sampling mosquito larvae and pupae to determine the trends of immature population, weekly after treatments and before treatments.